Computational modelling of environment flows featuring gas dispersion - Gerousi, Loukia (Cranfield University, 2010)
This study particularly aims at understanding flow and pollutant dispersion when flat terrain, single hill and hill with obstacles are present. The emissions of ethylene from a point source are located in eight different positions. For the hill cases, the sources are located downwind from the top of the hill, and the data are collected at various locations. The commercial software packages Gambit 2.4.6, Fluent 6.3.26 and Tecplot 360 are used for the two-dimensional mesh generation, for the flow simulation and for the validation respectively. The numerical results are compared with experimental and numerical data for the single hill case and for the point source using the Spalart- Allmaras model, k-ε Standard, k-ε RNG and k-ε Realizable models. The comparison of the results shows that the k-ᵋ Standard model is in good agreement with the experimental and numerical data. Results also show that the mass fraction of ethylene is highest for the flat terrain case. The next highest mass fraction of ethylene is found for the case with the hill and obstacles, and the single-hill case has the lowest. Moreover, upwind of the first obstacle the average mass fraction is larger than inside the first and the second canyons, and the minimum pollutant is downwind of the last obstacle. The average mass fraction of ethylene is measured at the corners of the canyons, and the results show that generally the bottom left corners have a higher mass fraction than the middle and bottom right side.